2018
DOI: 10.1289/ehp1829
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Phthalates and the Development of Eczema Phenotypes in Male Children: Results from the EDEN Mother–Child Cohort Study

Abstract: Background:Contradictory results exist regarding the importance of early-life exposure to phthalates for development of childhood eczema.Objectives:We evaluated the association between maternal urinary concentrations of phthalate metabolites between the 24th and 28th week of gestation and occurrence of eczema in their sons up to 5 y of age, according to allergic sensitization as assessed by total immunoglobulin E (IgE) in a subsample of individuals.Methods:Data on health outcomes and background factors were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 66 publications
(90 reference statements)
2
25
1
2
Order By: Relevance
“…We did not find associations between phthalate exposure and asthma, probably because our mothers were less exposed and the diagnosis of asthma is difficult to verify before the children can collaborate [2]. Ten cohort studies [5,7,9,[11][12][13][14][15][16]19] examined the association between prenatal phthalate exposure and eczema. Two studies [14,16] measured exposure in serum and detected an association between high concentration of MEHP and DiNP metabolites and decreased risk of eczema.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…We did not find associations between phthalate exposure and asthma, probably because our mothers were less exposed and the diagnosis of asthma is difficult to verify before the children can collaborate [2]. Ten cohort studies [5,7,9,[11][12][13][14][15][16]19] examined the association between prenatal phthalate exposure and eczema. Two studies [14,16] measured exposure in serum and detected an association between high concentration of MEHP and DiNP metabolites and decreased risk of eczema.…”
Section: Discussionmentioning
confidence: 87%
“…Two studies [14,16] measured exposure in serum and detected an association between high concentration of MEHP and DiNP metabolites and decreased risk of eczema. Three studies [11][12][13] found that higher urinary concentrations of MBzP, MEP, MiBP and ΣDEHP m was associated with increased odds of eczema in 2-5 years old children. One study [5] suggested that higher urinary MBzP concentration increased the risk of eczema in 2-year old but not 5year old children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…foodstuff) or exposures caused by individual life style (i.e. medical history, demographic data, socioeconomic status, product use) pivotal in identifying causes of disease particularly in cohort studies (Soomro et al, 2018;.…”
Section: Different Approaches To Assess Human Exposure To Phthalatesmentioning
confidence: 99%